MORALITY OF FATWA IN THE ISLAMIC LAW THINKING - Khoiruddin Nasution; Masnun Tahir (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2010)
In the recent years, certain people or institutions tend to give fatwa hastily. Those people are very easy to determine whether something is ‘halal’ or ‘haram’, although they tend to disobey the ethics of giving fatwa. They do not even have qualification or authority as mufti. This situation attracts concern. This tendency should be ended. Fatwa is a method in The Qur’an and as-Sunnah to explain syara’; hence fatwa should not be produced by people or bodies who do not have religious authority. A mufti must obey the rules and ethics of giving fatwa. This writing discusses how the position of fatwa in Islam and in the human’s life as well as the academic rules and ethics of a mufti.